PARALLEL COMPUTING FOR BLURRING IMAGE USING MEAN AND WEIGHTED AVERAGE METHOD - SYAHZIAR, M. REZA; GUNAWAN, P. H. (E-Jurnal Matematika; Vol 7 No 1 (2018), 2018)
Blurring is one of the basic image processing technique in order to reduce the noise in a image. In this paper two methods of blurring which are called mean and weighted average method will be elaborated. Three different sizes of mask (3 × 3, 5 × 5 and 7 × 7) are given for each method. Moreover, three different of resolution images 1000 × 1000, 700 × 700, and 400 × 400 pixels are used. From the experiment result, the output image by mean method is shown a darker than the weighted average method. Additionally, run time of CPU using mean method is around 77.78 % shorter than weighted average method.